PRÊMIO TOP EMPRESARIAL: UM ESTUDO DE CASO SOBRE AS EMPRESAS DE SERVIÇOS VENCEDORAS DO ESTADO DO RIO DE JANEIRO. - Oliveira, Carlos Henriques Ventura do Rosário (2004)
Considering all the sectors of the economy, the sector of services is responsible for a great parcel of the Brazilian s national PIB (IBGE, 2002). Organizations of this sector has looked for to get prominence in the market, through the search of management methods, aligned with search for excellence and quality, what can be confirmed by the increasing number of small organizations in Rio de Janeiro applying to the TOP Empresarial Award. This research was developed based on the Criteria for Excellence of the PNQ Quality Award, by evaluating the services organizations that had received the TOP Empresarial award in the Rio de Janeiro in 2001, 2002 and 2003, having been investigated the periods from the applying process and awarding. The research also covered the results of the organizations from the sector of services that had participated of the prize in 2003 and 2004. The study showed that small service organizations in Rio de Janeiro are looking for differentiation in the market, through the search of quality, showing good results in the winning organizations. The study also indicated that there is a gap between management models of the services organizations and the model suggested by the PNQ.